Solve the following equations 4x - 3 = 3x + y = x - y = 3...
Solve the following equations 4x - 3 = 3x + y = x - y = 3, 3x + y = 2y + 5x - 12
x = 5, y = 2
x = 2, y = 5
x = 5, y = -2
x = -2, y = -5
x = -5, y = -2
Correct answer is A
4x - 3 = 3x + y = x - y = 3.......(i)
3x + y = 2y + 5x - 12.........(ii)
eqn(ii) + eqn(i) 3x = 15
x = 5
substitute for x in equation (i)
5 - y = 3
y = 2
Alfred spent 14 of his money on food, 13 on clothing and save the rest. If...
Which of the following is not a sufficient condition for two triangles to be congruent? ...
Find the probability that a number selected at random from 21 to 34 is a multiple of 3...
The graph above is that of a quadratic function y = 2x2 - x - 6 The roots of the equation are...